Potential of Li-Fi (Light Fidelity) Technology for Internet Penetration in Rural India - Akram, W (International Journal of Computer Sciences and Engineering, 2019)
Li-Fi stands for Light-Fidelity. Li-Fi is a data transfer technology that uses visible light as the medium of transfer rather than the radio waves that are used currently in the Wi-Fi technology [1]. This technology is cheaper, cleaner, greener, faster and secure than the Wi-Fi technology. Digital India is a much celebrated and much discussed programme of Indian Government that focuses on internet penetration in the remotest corners of India. This paper presents a survey of the applications, advantages, disadvantages and standardization of Li-Fi. It also focuses on the research challenges in VLC. In this paper, a study on how Li-Fi Technology can be used in rural areas for the transformation of India into a Digital India by using Li-Fi enabled Solar Panels has been carried out. In this paper we cover every aspect of implementation of Li-Fi Technology in rural India. During this paper we explain how this emerging technology will empower the rural areas in a broad way.